2016
DOI: 10.1158/1535-7163.mct-15-0877
|View full text |Cite
|
Sign up to set email alerts
|

MiR-548an, Transcriptionally Downregulated by HIF1α/HDAC1, Suppresses Tumorigenesis of Pancreatic Cancer by Targeting Vimentin Expression

Abstract: Hypoxic microenvironments contribute to the tumorigenesis of numerous cancers by regulating the expression of a subset of miRNAs called "hypoxiamiRs." However, the function and mechanism of these deregulated miRNAs in hypoxic microenvironments within pancreatic cancers remain undefined. This study demonstrates that miR-548an is significantly downregulated in pancreatic cancer tissues and correlates with increased tumor size, advanced TNM stage, distant metastasis, and poor prognosis. Moreover, the overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…It has been recently reported that activated p-ERK and p-p38 MAPK signaling pathways and E-cadherin take part in regulating proliferation, migration, and invasion of PANC-1 cells [33]. In addition, downregulation of vimentin suppresses the proliferation and invasion of PC cells in vitro and in vivo [34]. Oncogenic K-Ras enhances the malignant phenotype and the mitogen-activated protein kinase p38 was identified as a target to inhibit oncogenic K-Ras -induced pancreatic cancer cell migration [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that activated p-ERK and p-p38 MAPK signaling pathways and E-cadherin take part in regulating proliferation, migration, and invasion of PANC-1 cells [33]. In addition, downregulation of vimentin suppresses the proliferation and invasion of PC cells in vitro and in vivo [34]. Oncogenic K-Ras enhances the malignant phenotype and the mitogen-activated protein kinase p38 was identified as a target to inhibit oncogenic K-Ras -induced pancreatic cancer cell migration [35].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from transcriptional regulation of vimentin expression by EMT-related transcriptional drivers, vimentin expression can be regulated also by non-coding microRNAs (miRs). It has been proposed that the HIF-1a-HDAC1 complex transcriptionally inhibits miR-548an expression during hypoxia, resulting in the upregulation of vimentin that facilitates pancreatic tumorigenesis [26]. Likewise, and miR-138 [28] were found to oppose EMT by partially suppressing vimentin expression.…”
Section: Vimentin In Emtmentioning
confidence: 99%
“…It has been demonstrated that vimentin promoter methylation inversely correlates with vimentin expression and disease progression in gastric cancer [25].Apart from transcriptional regulation of vimentin expression by EMT-related transcriptional drivers, vimentin expression can be regulated also by non-coding microRNAs (miRs). It has been proposed that the HIF-1a-HDAC1 complex transcriptionally inhibits miR-548an expression during hypoxia, resulting in the upregulation of vimentin that facilitates pancreatic tumorigenesis [26]. Likewise, and miR-138 [28] were found to oppose EMT by partially suppressing vimentin expression.Recent data suggest that Twist, one of the main EMT drivers, promotes EMT not only by E-cadherin suppression but also by negative regulation of vimentin miRs.…”
mentioning
confidence: 99%
“…HIF-1α can directly inhibit the expression of miR-34a in p53-defective colorectal cancer cells, whereas the level of miR-34a is increased in p53proficient colorectal cancer cells under hypoxia [66]. HIF-1α could recruit HDAC1 to the promoter of pri-miR-548an to transcriptionally suppress miR-548an expression, resulting in the upregulation of the EMT marker vimentin, which facilitates the proliferation and invasion of pancreatic cancer cells [67]. Dicer, an RNase III enzyme responsible for cytoplasmic processing of precursor miRNA [79], is frequently interfered with by HIF-1α in an indirect manner [68].…”
Section: Regulation Of Other Hrm Expression By Hif-1αmentioning
confidence: 99%
“…HRNs are of great significance in evaluating the prognosis of tumors. In pancreatic cancer, the expression of miR-646 [181] and miR-548 [67] is correlated with clinicopathological indicators such as TNM stage and overall survival (OS), and hypoxia-induced lncRNA NUTF2P3-001 overexpression also indicates advanced TNM stage and shorter survival time of patients [88]. Both Low expression of miR-592 [144] and high expression of miR-130b [184] can bring about poorer OS in hepatocellular carcinoma patients.…”
Section: Perspectives On Hif-1α and Ncrnas In Clinical Practicementioning
confidence: 99%